Nationwide study of haemolytic uraemic syndrome: clinical, microbiological, and epidemiological features. Issue 2 (1st August 2001) - Elliott, E J; Robins-Browne, R M; O'Loughlin, E V; Bennett-Wood, V; Bourke, J; Henning, P; Hogg, G G; Knight, J; Powell, H; Redmond, D; ,
Abstract : AIMS: To establish the incidence and aetiology of haemolytic uraemic syndrome (HUS) in Australia and compare clinical and microbial characteristics of sporadic and outbreak cases. METHODS: National active surveillance through the Australian Paediatric Surveillance Unit with monthly case notification from paediatricians, July 1994 to June 1998. Children under 15 years presenting with microangiopathic haemolytic anaemia, thrombocytopenia, and acute renal impairment were identified. RESULTS: Ninety eight cases were identified (incidence 0.64 per 10 5 children <15 years/annum and 1.35 per 10 5 children <5 years/annum). Eighty four were associated with diarrhoea (64 sporadic, 20 constituting an outbreak) and 14 were atypical. Shiga toxin producing Escherichia coli (STEC) O111:H− was the most common isolate in sporadic HUS and caused the outbreak. However O111:H− isolates from outbreak and sporadic cases differed in phage type and subtyping by DNA electrophoresis. STEC isolates from sporadic cases included O26:H−, O113:H21, O130:H11, OR:H9, O157:H−, ONT:H7, and ONT:H−. STEC O157:H7 was not isolated from any case. Only O111:H− isolates produced both Shiga toxins 1 and 2 and possessed genes encoding E coli attaching and effacing gene (intimin) and enterohemolysin. Outbreak cases had worse gastrointestinal and renal disease at presentation and more extrarenal complications. CONCLUSIONS: Linking national surveillance with a specialised laboratory service allowed estimation of HUS incidence and provided information on its aetiology. In contrast to North America, Japan, and the British Isles, STEC O157:H7 is rare in Australia; however, non-O157:H7 STEC cause severe disease including outbreaks. Disease severity in outbreak cases may relate to yet unidentified virulence factors of the O111:H− strain isolated.